Does Posterior Condylar Offset Affect Clinical Results following Total Knee Arthroplasty? - Degen, Ryan M.; Matz, Jacob; Teeter, Matthew G.; Lanting, Brent A.; Howard, James L.; McCalden, Richard W. (The Journal of Knee Surgery, 2018)
Total knee arthroplasty (TKA) is an effective, durable treatment for knee osteoarthritis. However, a subset of patients experiences incomplete pain relief and ongoing dysfunction. Posterior condylar offset (PCO) has previously been shown to be associated with postoperative range of motion (ROM) following TKA; however, an association with patient-reported outcome measures (PROMs) has not been established. The purpose of this study was to evaluate the association between PCO and postoperative ROM and PROMs. A retrospective review of 970 posterior-stabilized single design TKAs was performed. Preoperative and postoperative radiographs were analyzed to measure the change in PCO and anteroposterior (AP) femoral dimension. Clinical outcome measures, including Short Form-12 physical and mental component summaries, Western Ontario and McMaster Universities Arthritis Index, and Knee Society Score were reviewed to determine if these were influenced by changes in PCO and AP dimension. PCO was increased by more than 3 mm in 15.1%, maintained (within 3 mm) in 59.6%, and decreased by more than 3 mm in 25.3% of patients. Comparing between these groups, there were no significant differences in postoperative ROM or PROM. AP dimension increased in 24.4%, maintained in 47.8%, and decreased in 27.8%. Similarly, there were no significant differences in ROM or PROM between these groups. Spearman's correlation analyses failed to identify an association between PCO and ROM or PROMs. In conclusion, increasing or decreasing PCO or AP femoral dimension with this PS TKA design did not significantly affect postoperative ROM or PROM. Similarly, maintenance of PCO within one implant size with this system compared with optimal sizing had no deleterious effect on TKA outcomes.
Keywords: total knee arthroplasty; posterior femoral offset; posterior condylar offset; outcomes